The Impact of Early Childbearing on Schooling and Cognitive Skills among Young Women in Madagascar - Catalina Herrera; David E. Sahn (Institute for the Study of Labor (IZA), 2015)
Female secondary school attendance has recently increased in Sub-Saharan Africa and so has the risk of becoming pregnant while attending school. Using panel data in Madagascar, we analyze the impact of teenage pregnancy on young women's human capital. We instrument early pregnancy with the young woman's community-level access, and exposure to condoms since age 15. We control for an extensive set of community social and economic infrastructure characteristics to deal with the endogeneity of program placement and conduct several robustness checks to validate our instruments. Early childbearing increases the likelihood of dropping out of school by 42 % and decreases the chances of completing secondary school by 44%. This school-pregnancy related dropout is associated with a reduction of 1.1 standard deviations in Math and French test scores. Delaying the first birth by a year increases the probability of current enrollment by 5% and the test scores by 0.2 standard deviations.
Keywords: I25; J13; O15; 330; fertility; female education; cognitive skills; instrumental variables; Madagascar